COMPARISON OF DIAGNOSTIC VALUE OF SHEAR WAVE ELASTOGRAPHY AND LIVER BIOPSY IN ASSESSING LIVER FIBROSIS - ZAHRA, M; ZAFAR, A; KHALID, A; AHMED, R; BUKHARI, A (Biological and Clinical Sciences Research Journal, 2022)
This prospective study was designed to compare the specificity and sensitivity ofshear wave elastography(SWE) and liver biopsy in liver fibrosis staging. The study was conducted at Bakhtawar Amin Trust Hospital Multan from July 2021 to July 2022. The study was conducted on 90 patients who underwent liver biopsy due to pathologies, including congenital liver diseases or as possible liver donors. An experienced radiologist performs shear wave elastography. An experienced histopathologist assessed biopsy specimens. The mean age of the patients was 30 years. Out of 90 patients, 16 (17.7%) had Hep B or C, 20 (22.2%) were liver donors, and 54 (60%) had other liver diseases. Elastography results showed mean liver stiffness in F0–F1, F2, F3, and F4 stage fibrosis to 5.48 ± .52 kPa, 8.22 ± .42 kPa, 9.56 ± .32 kPa, and 12.41 ± 2.9kPa, respectively. Results of liver biopsy and SWE were significantly correlated (p=.0001).Shear wave elastography is an effective tool for the assessment of liver fibrosis.